2020
DOI: 10.1039/d0cp04012f
|View full text |Cite
|
Sign up to set email alerts
|

Viscosity effects on optically generated electron and nuclear spin hyperpolarization

Abstract: Optically-generated dynamic nuclear polarization is increased in viscous mixtures due to longer lived electron spin polarization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(15 citation statements)
references
References 52 publications
(81 reference statements)
1
14
0
Order By: Relevance
“…This suggests that controlling the dynamics as well as the distance between the dye and the radical is important for both efficient DEP and long-lasting DEP. Based on the findings obtained in this study, we expect that the optimization of various dyes and radicals linked by flexible linkers will lead to the application of large and sustained DEP to ESR imaging and light-driven DNP. …”
Section: Discussionmentioning
confidence: 82%
See 4 more Smart Citations
“…This suggests that controlling the dynamics as well as the distance between the dye and the radical is important for both efficient DEP and long-lasting DEP. Based on the findings obtained in this study, we expect that the optimization of various dyes and radicals linked by flexible linkers will lead to the application of large and sustained DEP to ESR imaging and light-driven DNP. …”
Section: Discussionmentioning
confidence: 82%
“…In addition, the ESR signal in the unlinked systems decayed within a few microseconds, whereas the ESR signal in the hybridized systems was observed for more than 10 μs. It has been reported that the integrated ESR signal over time is a good indicator of optically generated DNP, and hybridized systems are expected to show much better DNP performance than unlinked systems.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations